2007
DOI: 10.1021/jo062616y
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Three-Component One-Pot Benzylation and Allylation of Aldehydes and Amines for Synthesis of Homobenzylamines and Homoallylamines

Abstract: A highly efficient, three-component one-pot benzylation and allylation of aromatic and aliphatic aldehydes and amines affords the corresponding homobenzylamines and homoallylamines in good to excellent yield. The procedure is lauded by its simplicity and manipulability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 9 publications
1
27
1
Order By: Relevance
“…The substrate 32 was synthesized in 3 steps as shown in Scheme . A three‐component coupling reaction between benzyl bromide, 2‐furfural, and 4‐methoxyaniline in the presence of zinc dust in THF, gave amine 30 in 78 % yield 38. Acylation with ( Z )‐3‐iodoacryl chloride3 in the presence of Cs 2 CO 3 provided 31 (45 %), which was further heated (100 °C) to promote an intramolecular Diels–Alder reaction to furnish 32 in 28 % yield, accompanied by isomeric 8‐ epi ‐ 32 in 51 % yield.…”
Section: Discussionmentioning
confidence: 99%
“…The substrate 32 was synthesized in 3 steps as shown in Scheme . A three‐component coupling reaction between benzyl bromide, 2‐furfural, and 4‐methoxyaniline in the presence of zinc dust in THF, gave amine 30 in 78 % yield 38. Acylation with ( Z )‐3‐iodoacryl chloride3 in the presence of Cs 2 CO 3 provided 31 (45 %), which was further heated (100 °C) to promote an intramolecular Diels–Alder reaction to furnish 32 in 28 % yield, accompanied by isomeric 8‐ epi ‐ 32 in 51 % yield.…”
Section: Discussionmentioning
confidence: 99%
“…The first true multicomponent preparation of β‐arylethylamines was reported by Fan, Wu, and co‐workers in 2007 . Their one‐pot benzylation and allylation protocol involved the generation of an organozinc reagent in situ under Barbier conditions together with an aminal, with the organometallic species acting both as a nucleophile and as a dehydrating agent.…”
Section: Sp3 Nucleophilesmentioning
confidence: 99%
“…Recently, Mandai et al 35 The addition of organometallic reagents to imines is a versatile method for the CeC bond-formation reactions. Fan et al 36 reported a three-component, one-pot benzylation and allylation of aromatic and aliphatic aldehydes and amines under Barbier-type conditions using zinc powder to yield 45 (Scheme 16). Over the years, significant advances have been made in the Barbiertype imine alkylations.…”
Section: Electrophilic Nature Of Imine In Mcrsmentioning
confidence: 99%